The singular ideal and the socle of incidence rings - Kanuni, Muge; Ozkan, Ozkay (Hacettepe Univ, Fac Sci, 2021)
Let R be a ring with identity and I(X, R) be the incidence ring of a locally finite partially ordered set X over R. In this paper, we compute the socle and the singular ideal of the incidence ring for some X in terms of the socle of R and the singular ideal of R, respectively.
Keywords: incidence ring; socle; singular ideal